1998
DOI: 10.1159/000028434
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Rhythmic Behavior and Canonical Babbling in Infant Vocal Development

Abstract: The onset of canonical babbling (CB) is a landmark event in infants’ vocal development for spoken language. Previous research has suggested that the onset of CB coincides with the peak period of rhythmic activities. To examine this phenomenon in detail, 28 Japanese infants (14 girls, 14 boys) were observed longitudinally from the age of 5 to 9 months. In the experimental sessions, an audible or an inaudible rattle was placed into a hand of each tested infant. Then the number of times that the infant shook the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 27 publications
4
50
0
2
Order By: Relevance
“…Since these are prime conditions for entrainment, production of repetitive, rhythmically organized arm movements gradually entrains vocal activity, leading eventually to the emergence of the rhythmically organized CV sequences that comprise babbling. One would therefore expect the appearance of reduplicated babble to be accompanied by an increase in frequency of arm rhythmicity; and indeed, this is precisely what is observed in typically developing infants (e.g., Ejiri, 1998;Iverson, 2005;Thelen, 1979).…”
Section: Group Patterns Of Delaymentioning
confidence: 64%
“…Since these are prime conditions for entrainment, production of repetitive, rhythmically organized arm movements gradually entrains vocal activity, leading eventually to the emergence of the rhythmically organized CV sequences that comprise babbling. One would therefore expect the appearance of reduplicated babble to be accompanied by an increase in frequency of arm rhythmicity; and indeed, this is precisely what is observed in typically developing infants (e.g., Ejiri, 1998;Iverson, 2005;Thelen, 1979).…”
Section: Group Patterns Of Delaymentioning
confidence: 64%
“…As a first step, a child forms auditory images of speech sounds. Using an internal model, the child then experiments with how to integrate the percept of a sound with the proper way to manipulate the vocal apparatus to produce the sound (babbling) (Ejiri 1998;Guenther et al 1998). If the percept of a sound is disrupted (at any level), then production of that sound would undoubtedly be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Masataka (1995) found the association of index finger extension with syllabic vocalizations in threemonth-old babies. In addition, other studies have shown the association of canonical babbling and rhythmic manual movements between 6 and 9 months (Ejiri, 1998;Ejiri & Masataka, 2001), or suggest a mutual facilitation effect between motor and vocal development (Iverson & Fagan 2004;Iverson, Hall, Nickel, & Wozniak, 2007). Several motor and gestural milestones coemerge with language development milestones in early development (Bates & Dick, 2002).…”
mentioning
confidence: 98%